Literacy Assistance for Santri at the Nurul Yaqin Islamic Boarding School - Andy.N, Nofri; Basir, Gusril; Na'ali, Basri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
The lack of mastery of students related to literacy causes the messages contained in the turastbooks to not be fully conveyed to the community. This assistance aims to strengthen the skills of students,especially in writing so that they can put their ideas into written form. The methods used are lectures,demonstrations and exercises related to strengthening reading and writing. The result of this service is theability of students to write ideas that come from turast books so that they can understand Islamic valuesfrom primary sources.